Estudo comparativo do desempenho financeiro e social das empresas do setor elétrico brasileiro pós-privatizações no período de 2000 a 2003 - Fodra, Marcelo (2007)
The availability of energy is a crucial element to the economic development of societies. In Brazil, in particular, predominate the use of electric energy that comes from hydraulic sources, because of the huge natural hydric potential that existing in Brazil. Since the beginning of the 20 th century, the government legislated and controlled the electrical sector as a whole, maintaining all the productive structure by natural monopole, exploring the services and taxing for the use, doing important services to the economic and social development of the country. Yet, when the State lost its investment capability, the predominant attitude nowadays was adopted, promoting the privatization of several productive structures, including the national electric facility. To do so, legal and organization measures, were taken, mainly determination of unverticalization of organization, building a competitive environment not consolidated yet. This assignment tried to compare the social and economic performance levels reached by the public and private Brazilian electrical companies, focusing on the added value, from financial and social demonstration elaborated by coletive groups that operated on the generation and distribution of energy from the hydraulic sources, between 2000 and 2003